Cloud computing acceptance among public sector employees - Mohd Talmizie Amron; Roslina Ibrahim; Nur Azaliah Abu Bakar (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
Cloud computing is one of the platforms that drive organisations and users to be better prepared for a simpler computing platform and offers significant benefits to the quality of work. The transition from conventional computing to the virtual world helps organisations to maximise their potential. However, not all users can accept cloud computing adoption. Failure to understand the factors of user's acceptance will negatively impact the organisation's mission of empowering the technology. Therefore, this study proposes to assess to what extent the users are accepting cloud computing. This study adopts the unified theory of acceptance and use of technology (UTAUT) and six technological and human factors assessed for the Malaysian public sectors. Survey data from several ministries were analysed using partial least squares-structural equation modelling (PLS-SEM). The study found out that performance expectancy, compatibility, security, mobility, information technology (IT) knowledge, and social influence had a significant impact on the user's intention to accept cloud computing. The results of this study contribute to a clear understanding of the factors affecting the Malaysian public sectors about cloud computing.